Release of Full-Length PrPC from Cultured Neurons Following Neurotoxic Challenge - Wang, Kevin K.; Zoltewicz, Susie; Chiu, Allen; Zhang, Zhiqun; Rubenstein, Richard (Frontiers in Neurology, 2012)
The susceptibility of the normal cellular prion protein isoform, PrPC, to proteolytic digestion has been well documented. In addition, a link between PrPC and the cytosolic protease, calpain, has been reported although the specifics of the interaction remain unclear. We performed in vitro and in cell-based studies to examine this relationship. We observed that human recombinant PrP (HrPrP) was readily cleaved by calpain-1 and -2, and we have identified and defined the targeted cleavage sites. In contrast, HrPrP was resistant to caspase-3 digestion. Unexpectedly, when brain lysates from PrPC-expressing mice were treated with calpain, no appreciable loss of the intact PrPC, nor the appearance of PrPC breakdown products (BDPs) were observed, even though alpha II-spectrin was converted to its signature calpain-induced BDPs. In addition, when rat cerebrocortical neuronal cultures (RtCNC) were subjected to the two neurotoxins at subacute levels, maitotoxin (MTX) and N-methyl-D-aspartate (NMDA), PrPC BDPs were also not detectable. However, a novel finding from these cell-based studies is that apparently full-length, mature PrPC is released into culture media from RtCNC challenged with subacute doses of MTX and NMDA. Calpain inhibitor SNJ-1945 and caspase inhibitor IDN-6556 did not attenuate the release of PrPC. Similarly, the lysosomal protease inhibitor, NH4Cl, and the proteasome inhibitor, lactacystin, did not significantly alter the integrity of PrPC or its release from the RtCNC. In conclusion, rat neuronal PrPC is not a significant target for proteolytic modifications during MTX and NMDA neurotoxic challenges. However, the robust neurotoxin-mediated release of full-length PrPC into the cell culture media suggests an unidentified neuroprotective mechanism for PrPC.